1998
DOI: 10.1577/1548-8675(1998)018<0599:pafhia>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and Fish Health in a Desert Stream, and Management Implications for Two Endangered Fishes

Abstract: Reintroductions of the endangered razorback sucker Xyrauchen texanus and Colorado squawfish Ptychocheilus lucius into the Verde River, Arizona, have failed to establish self‐sustaining populations. The failure of these reintroductions is often attributed to predation and competition by nonnative fishes and habitat loss, but parasite infestations (particularly a copepod, Lernaea cyprinacea) also have been implicated. We assessed the relationships among fish health, eukaryotic parasites, and bacterial and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
(1 reference statement)
1
14
0
Order By: Relevance
“…Predation and competition by nonnative fishes are considered as potentially serious threats to native populations of fish (Robinson et al 1998), and there are many examples where barriers have been used as control techniques to address these issues. These can include electrical barriers (), stone filled gabions (), and the use of stop logs placed in small streams (Buktenica 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Predation and competition by nonnative fishes are considered as potentially serious threats to native populations of fish (Robinson et al 1998), and there are many examples where barriers have been used as control techniques to address these issues. These can include electrical barriers (), stone filled gabions (), and the use of stop logs placed in small streams (Buktenica 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The necropsy-based technique was modified by Adams et al (1993) to provide a quantitative health assessment index (HAI) allowing statistical comparisons of data among fish populations. The Goede and Barton (1990) procedure was based primarily on data derived from salmonid fishes, but modifications of the method have been applied to coldwater and warmwater fishes (Adams et al 1993;Coughlan et al 1996;Robinson et al 1998). No consistent approach to assessment of fish health has yet emerged, and distinctions between health and condition are unclear in relation to various health assessment procedures (Goede and Barton 1990;Adams et al 1993;Coughlan et al 1996).…”
mentioning
confidence: 99%
“…In contrast, a fish condition index was excluded from the HAI developed by Adams et al (1993). Robinson et al (1998) found no significant correlation between K and an HAI in seven riverine fishes.…”
mentioning
confidence: 99%
See 2 more Smart Citations